Conditions for Forming Readiness for Professional Pedagogical Activity in Pedagogical Students - Турдалиев Араббой Адхам угли (Periodica Journal, 2022)
This article discusses at the present time scientists are conducting pedagogical research related to the problems of improving the functioning of pedagogical systems and how to increase the productivity of learning, most of all attention is attracted by the creation, explanation and control of the educational environment, which should help in further activities.
Keywords: Student; Readiness For A Professional; Professional; Readiness